FINANCIAL MECHANISMS FOR SUPPORTING SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Alikulov Khazrat Amirkulovich (Journals Park Publishing, 2025)
This article analyzes the role and importance of modern financial mechanisms in supporting small businesses and private entrepreneurship. The study shows the advantages of modern approaches such as digital finance, fintech services, crowdfunding, venture capital, Islamic finance, green finance, and international financial institutions. It is also substantiated that these financial mechanisms create favorable conditions for small businesses, expand opportunities for attracting investments, and serve the sustainable development of the economy. At the end of the article, conclusions and practical proposals for improving the system of support for small businesses are presented.
Keywords: Small business, private entrepreneurship, modern financial mechanisms, digital finance, crowdfunding, venture capital, Islamic finance, green finance, investment, international financial institutions, sustainable development.